Institutionalism and its effect on labour forecasting in Vietnamese firms. (October 2020) - Nguyen, Bach; Do, Hoa
This study examines factors that influence firm forecasting regarding their labour expansion in Vietnam. Conventional wisdom has it that foreign-owned and large private firms make more accurate forecasts since they have more resources and experience than their smaller and state-owned counterparts. However, this study empirically shows that state-owned and small firms make more accurate forecasting values. There are two possibilities that can explain this counterintuitive result: (1) the institutional incompleteness in the post-communist economy and (2) systematic underestimation of their own performance by foreign and large private firms, which results from the institutional complexity in Vietnam. These unique findings provide valuable information for both academia and practitioners.